2021
DOI: 10.1146/annurev-psych-080520-102803
|View full text |Cite
|
Sign up to set email alerts
|

Prejudice and Discrimination Toward Immigrants

Abstract: Prejudice and discrimination toward immigrants, and the consequences of these negative attitudes and behavior, are key determinants of the economic, sociocultural, and civic-political future of receiving societies and of the individuals who seek to make these societies their new home. In this article I review and organize the existing literature on the determinants and nature of prejudice and discrimination toward immigrants, summarizing what we know to date and the challenges in attributing effects to immigra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
115
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(123 citation statements)
references
References 142 publications
6
115
0
2
Order By: Relevance
“…Fourth, one of our inclusion criteria was that mothers and children had migrated to Hong Kong within 7 years; this decision was based on the assumption that after individuals receive permanent resident status, they may no longer be viewed as “outsiders” in their new cultural context. Being recognized as a permanent resident may increase migrants’ social status, thereby leading to fewer experiences of discrimination (Esses, 2020). Our reasoning, however, is speculative and needs to be empirically tested.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourth, one of our inclusion criteria was that mothers and children had migrated to Hong Kong within 7 years; this decision was based on the assumption that after individuals receive permanent resident status, they may no longer be viewed as “outsiders” in their new cultural context. Being recognized as a permanent resident may increase migrants’ social status, thereby leading to fewer experiences of discrimination (Esses, 2020). Our reasoning, however, is speculative and needs to be empirically tested.…”
Section: Limitationsmentioning
confidence: 99%
“…Perceived discrimination is an individual's subjective experience of being unfairly treated based on membership in a social group (derived from actual or perceived experiences) and is significantly related to negative outcomes among immigrants (Esses, 2020; Schmitt et al, 2014). Previous studies identified a positive association between perceived discrimination and various adverse outcomes among migrants (Lee & Ahn, 2011; Pascoe & Smart Richman, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allport (1954) posits that negative attitudes towards a different social group-in the context of this study, against immigrants-can be ameliorated through intergroup contact, in which individuals interact with people from the other social group. However, it is vital to consider the context and quality of contact, as not all contact promotes positive perceptions, and negative contact has the possibility to negatively affect intergroup relations (Esses, 2021;Robinson et al, 2020). For example, Kiehne's (2019) research on anti-immigrant prejudice in university students provides evidence linking intergroup contact with reduced anti-immigrant prejudice.…”
Section: Intergroup Contactmentioning
confidence: 99%
“…Much research seeks to explain individuals' attitudes toward immigrants and immigration (for reviews, see Hainmueller and Hopkins, 2014;Esses, 2021) and, more recently, public opinion toward religious symbols (Bilodeau et al, 2018;Ferland, 2018;Turgeon et al, 2019). While the attitudes of the general public are of great interest, demographic shifts brought on by migration are spurring significant changes in the composition of the electorate, posing new questions about what motivates politicians to recognize the needs of immigrants and religious minorities.…”
Section: Introductionmentioning
confidence: 99%